2023
DOI: 10.1186/s13765-022-00750-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of climatic factors on essential oil content and composition of 20 populations of Nepeta binaludensis Jamzad from Iran

Abstract: Nepeta binaludensis Jamzad is an endemic and rare perennial plant belonging to the Lamiaceae family, which grows in a limited area in Binaloud Mountain in northeast of Iran. In this study to evaluate the diversity of 20 populations (localities) of N. binaludensis and the influence of environmental factors on essential oil (EO) content and composition, the plant aerial parts were collected at the full flowering stage. The plant materials dried in shade and subjected to hydro-distillation for obtaining their EOs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Among the dominant components, the content of camphor in the essential oil linked to changes in climatic parameters (Table 2). The obtained results showed that the influence of climatic factors on the composition of EOs in plants was varying, which was also shown for plants of the genus Nepeta [26] and Lavandula [27]. Significant differences in the composition of EOs of plants from the Eravninsky district compared to the Selenginsky and Ivolginsky districts may be related to the fact that negative values of the average annual temperature lead to the existence of permafrost in the soils of the Eravninsky district, where permafrost has discontinuous distribution.…”
Section: Composition Of Essential Oils Of a Frigida From Different Po...mentioning
confidence: 65%
“…Among the dominant components, the content of camphor in the essential oil linked to changes in climatic parameters (Table 2). The obtained results showed that the influence of climatic factors on the composition of EOs in plants was varying, which was also shown for plants of the genus Nepeta [26] and Lavandula [27]. Significant differences in the composition of EOs of plants from the Eravninsky district compared to the Selenginsky and Ivolginsky districts may be related to the fact that negative values of the average annual temperature lead to the existence of permafrost in the soils of the Eravninsky district, where permafrost has discontinuous distribution.…”
Section: Composition Of Essential Oils Of a Frigida From Different Po...mentioning
confidence: 65%